Quo vadis quantum mechanics? - Dolev S; Elitzur A; Kolenda N (Berlin Springer-Verlag, 2005)
This book represents the combined efforts of sixteen of today's most eminent theoretical physicists to lay out future directions for quantum physics. The authors include Yakir Aharonov, Anton Zeilinger; the Nobel laureates Anthony Leggett and Geradus 't
Keywords: Quantum mechanics